A Comparison of Laboratory‐Based and Home‐Based Tests of Consumer Preferences Using Kid and Lamb Meat. Issue 3 (5th May 2014) - Guerrero, A.; Campo, M.M.; Cilla, I.; Olleta, J.L.; Alcalde, M.J.; Horcada, A.; Sañudo, C.
Abstract The meat from 60 commercial suckling males of five Spanish goat breeds (n = 10 each) (Moncaína [MO], Pirenaica [PI], Negra Serrana [NS], Blanca Celtibérica [BC] [all meat or double purpose] and Murciano‐Granadina [MG] [dairy purpose]) and one dairy sheep breed (Churra [CH]) was compared in laboratory‐based (n = 119) and home‐based (n = 70) consumer tests. In the laboratory, flavor (P ≤ 0.01), tenderness (P ≤ 0.001) and overall acceptability (P ≤ 0.001) differed significantly among the breeds, and MO, NS, MG and CH had the highest overall acceptability. In the home‐based test, tenderness (P ≤ 0.01) and overall acceptability (P ≤ 0.05), but not flavor, differed significantly among the breeds, and MO, BC, MG and CH had the highest overall acceptability. In conclusion, the two consumer test evaluated were adequate for evaluating meat acceptability from suckling small ruminants, having comparable results, although consumer preferences were slightly higher and signification levels slightly lower under home conditions than under laboratory conditions. Practical Applications Consumer acceptance is a big aim of any food sector. Meat is a complex product to be evaluated because of its intrinsic variability and because it needs to be cooked previously to be assessed. Comparisons with the same animals, in different circumstances: cut, type of cooking and temperature, condiments, ambiance, as it occurs in home tests or laboratory tests hardly exist. In this paper, the same results have been obtained in both tests with meat from small ruminants. This will undoubtedly favor the development of meat consumer tests in the future.